An intuitionistic fuzzy set–based hybrid approach to the innovative design evaluation mode for green products. (12th April 2016) - Wang, Ching-Hsin
As technology vigorously develops and the awareness of environmental protection rises, green industry has been gradually valued by government and consumers. Customers' needs can be satisfied with effective resource strategies as well as innovative technology of green products. Importance–performance analysis is a method incorporating the voices of customers and resource strategies of green design into the product development as well as management performance assessment by means of "importance" and "performance." Quality function deployment can turn the voices of customers into product development and technical requirement, in order to ensure that the product can meet customers' satisfaction. The present companies take not only customers' demand but also their own technical limits into account. Hence, data envelopment analysis can offer firms the priority order when they carry out their improvement in the green product design. Nevertheless, many uncertainties and semantic ambiguity appear in the process of information collection for the product design. Consequently, this study comes up with importance–performance analysis, analytical network process, quality function deployment, and data envelopment analysis, to construct an evaluation mode of innovative design for green products based on intuitionistic fuzzy sets offering enterprises a practical reference for their green product design.